INFLUENCE OF SOCIO-ECONOMIC, FINANCIAL LITERACY, AND DIGITAL FINANCIAL LITERACY ON GEN Z'S INVESTMENT BEHAVIOR - Lieanto, Calvin Timothy; Kohardinata, Cliff (Accounting Study Program, Universitas Ciputra Surabaya, 2025)
This study aims to analyze the impact of income and financial literacy on investment behavior through digital financial literacy as a mediation. The rise of information technology has brought significant changes in all sectors, financial sector is one of them. The rise of fintech can ease the process of doing investment activity but, on the other side, harm the users if they are not aware of the platform they are using. Gen Z in Surabaya is the population in this research since Gen Z dominates the number of investors in the capital market. The research method used is quantitative, where the data was collected from questionnaires that were analyzed statistically using SEM-PLS in the SmartPLS 3 program. The sampling method used is purposive sampling involving 172 Gen Z respondents from Surabaya. The results indicate that income has a significant effect on investment behavior, while financial literacy does not have a significant effect on investment behavior. However, digital financial literacy has a significant effect on investment behavior. Income has a significant effect on investment behavior when digital financial literacy serves as the mediation variable, partially mediating the relation. As well as financial literacy also has a significant effect on investment behavior when digital financial literacy serves as the mediator. Research suggests Gen Z actively enhances their financial literacy through self-learning from online courses or similar platforms. On the other hand, financial institutions can provide an accessible platform that can be easily accessed by Gen Z to improve their digital financial literacy.